Bacillus enclensis sp nov., isolated from sediment sample - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel bacterial strain, designated SGD-1123(T) was isolated from Chorao Island, in Goa Province, India. The strain was found to be able to grow at 15-42 A degrees C, pH 5-12 and 0-12 % (w/v) NaCl. The whole cell hydrolysates were found to contain meso-diaminopimelic acid, galactose and arabinose. The major fatty acids were identified as iso-C-15:0 and anteiso-C-15:0, MK-7 was identified as the predominant menaquinone and the predominant polar lipids were identified as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified aminolipid. The genomic DNA G+C content was determined to be 44.6 mol%. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and further revealed that strain SGD-1123(T) had highest sequence similarity with Bacillus aquimaris, and forms a separate clade with its closest relatives i.e. B. aquimaris, Bacillus vietnamensis and Bacillus marisflavi, with which it shares 94.5, 94.1 and 94.1 % similarity respectively. The phylogenetic, chemotaxonomic and phenotypic analyses indicated that strain SGD-1123(T) represents a novel species within the genus Bacillus, for which the name Bacillus enclensis is proposed. The type strain is SGD-1123(T) (NCIM 5450(T)=CCTCC AB 2011125(T)).
Keywords: Bacillus sp; Marine sediment; Polyphasic

Fictibacillus enclensis sp nov., isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Srinivasan, Krishnamurthi; Tang, Shan-Kun; Lee, Jae-Chan; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel Gram-positive strain, designated NIO-1003(T), was isolated from a marine sediment sample collected from the Chorao Island, Goa Provence, India. Strain NIO-1003(T) was found to be strictly aerobic, motile, endospore-forming rods. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1003(T) belongs to the genus Fictibacillus and to be most closely related to Fictibacillus rigui KCTC 13278(T), Fictibacillus solisalsi KCTC 13181(T) and Fictibacillus barbaricus DSM 14730(T) with 98.2, 98.0 and 97.2 % similarity and 25, 28, 39 nucleotide differences respectively. Strain NIO-1003(T) was characterized by having cell-wall peptidoglycan based on meso-diaminopimelic acid and MK-7 as the predominant menaquinone. The polar lipid profile exhibited the major compounds diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. In addition, minor amounts of an aminophospholipid were detected. The major fatty acids were identified as ai-C-15:0, iso-C-15:0, ai-C-17:0 and C-16:0, supporting the grouping of strain NIO-1003(T) into the family Bacillaceae. The DNA G+C content of strain NIO-1003(T) was determined to be 42.6 mol%. On the basis of phenotypic properties, phylogeny and DNA-DNA hybridisation analysis, strain NIO-1003(T) is considered to represent a novel species of the genus Fictibacillus for which the name Fictibacillus enclensis sp. nov. is proposed. The type strain is NIO-1003(T) (= NCIM 5458(T) = DSM 25142(T)).
Keywords: Chorao Island; Fictibacillus sp.; Polyphasic taxonomy

Rhodococcus enclensis sp nov., a novel member of the genus rhodococcus - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel actinobacterial strain, designated, NIO-1009(T), was isolated from a marine sediment sample collected from Chorao Island, Goa, India. Phylogenetic analysis comparisons based on 16S rRNA gene sequences between strain MO-1009(T) and other members of the genus Rhodococcus revealed that strain NI0-1009(T) had the closest sequence similarity to Rhodococcus kroppenstedtii DSM 44908(T) and Rhodococcus corynebacterioides DSM 20151(T) with 99.2 and 99.1%, respectively. Furthermore, DNA-DNA hybridization results showed that R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 20151(T) were 39.5 (3.0%) and 41.7 (2.0%) with strain NIO-1009(T), respectively, which were well below the 70% limit for any novel species proposal. Phylogenetically strain NIO-1009(T) forms a stable clade with and R. kroppenstedtii DSM 44908(T) and R. corynebacterioides DSM 201511 with 100% bootstrap values. Strain NI-1009(T) contained meso-diaminopimelic acid as the diagnostic diamino acid and galactose and arabinose as the cell wall sugars. The major fatty acids were C-16:0, C-18:1 omega 9c, C-16:1(omega 6C and/or omega 7c) and 10-methyl C-18:0. The only menaquinone detected was MK-8(H-2), while the major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and one unknown phospholipid. The G + C content of the genomic DNA was 66.9 molok. The phenotypic and genotypic data showed that strain NIO-1009(T) warrants recognition as a novel species of the genus Rhodococcus for which the name Rhodococcus enclensis sp. nov., is proposed; the type strain is NIO-1009(T) (=NCIM 5452(T)=DSM 45688(T)).

Bacillus filamentosus sp nov., isolated from sediment sample - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-stain positive, endospore-forming bacterium, designated SGD-14(T), was isolated from a marine sediment sample in Goa Province, India. Cells of the isolate were found to be strictly aerobic. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain SGD-14(T) showed a similarity of 99.5 % with Bacillus endophyticus and similarities to other Bacillus type strains were below 96 %. The whole-cell sugar pattern was found to consist of ribose, xylose and glucose. The predominant menaquinone was identified as MK-7 and the major fatty acids as anteiso-C-15:0, iso-C-15:0, iso-C-16:0, anteiso-C-17:0, C-16:0 and iso-C-14:0. The strain was found to grow optimally at 30 A degrees C and pH 7.0-7.5. DNA G + C content was determined to be 39.6 mol%. The phospholipid pattern was found to consist of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. DNA-DNA hybridization studies between strain SGD-14(T) and B. endophyticus CIP106778(T) showed that strain SGD-14(T) exhibited < 70 % similarity with B. endophyticus CIP106778(T). Differences in phenotypic and chemotaxonomic characteristics between the novel strain and B. endophyticus CIP106778(T) further confirmed that this isolate represents novel species. Phylogenetic analysis showed that strain SGD-14(T) fits in the same clade with B. endophyticus with 100 % bootstrap values. Strain SGD-14(T) is therefore considered to represent a novel species of the genus Bacillus, for which the name Bacillus filamentosus sp. nov. is proposed. The type strain of Bacillus filamentosus is SGD-14(T) = (=NCIM 5491(T) = DSM 27955(T)).
Keywords: Bacillus; Filaments; Polyphasic; Sediment

Deinococcus enclensis sp nov., isolated from a marine sediment sample - Thorat, Meghana N.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel pale-pink coloured strain, designated NIO-1023(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. The taxonomic position of strain NIO-1023(T) was investigated by using a polyphasic approach. The cells were observed to be Gram-stain positive, coccal shaped and non-spore forming. Phylogenetic analyses using the 16S rRNA gene sequence of the isolate indicated that the organism belongs to the genus Deinococcus. The strain NIO-1023(T) showed highest 16S rRNA gene sequence similarities with Deinococcus ficus (97.8 %), whereas other Deinococcus species showed less than 95 % sequence similarity. The DNA-DNA relatedness with respect to D. ficus CC-FR2-10(T) was 23.9 %. Chemotaxonomic data revealed that strain NIO-1023(T) contains only menaquinone MK-8 as the respiratory quinone and a complex polar lipid profile consisting of different unidentified glycolipids and polar lipids, two unknown phospholipids and three unknown phosphoglycolipids. As in other deinococci, one of these phosphoglycolipids was predominant in the profile. The predominant fatty acids were identified as C-17:1 w8c, C-16:1 w6c/w7c, C-15:1 w6c and C-17:1 w9c. The genomic DNA G + C content of strain NIO-1023(T) was determined to be 67.2 mol%. The biochemical and chemotaxonomic properties demonstrate that strain NIO-1023(T) represents a novel species, for which the name Deinococcus enclensis sp. nov. is proposed. The type strain is NIO-1023(T) (=DSM 25127(T) = NCIM 5456(T)).
Keywords: 16S rRNA; Deinococcus; Marine sediments; Polyphasic